Descrição de novas espécies de FidicinoidesBoulard & Martinelli (Hemiptera: Cicadidae) do Brasil - Santos, Rodrigo S.; Martinelli, Nilza Maria [UNESP] (Entomological Soc Brasil, 2009)
The examination of entomological collections of cicadas of several Brazilian institutions revealed three undescribed species in the genus Fidicinoides Boulard & Martinelli i.e., F. dolosa sp.n., F. carmenae sp.n. and F. rosabasalae sp.n. They are described and illustrated based on the male genitalia, the right anterior femur and the operculum.
Description of New Species of Fidicinoides Boulard & Martinelli (Hemiptera: Cicadidae) from Brazil
Keywords: Cicada; Morphology; Taxonomy